Biological outcomes of γ-radiation induced DNA damages in breast and lung cancer cells pretreated with free radical scavengers. (6th December 2018) - Petković, Vladana D.; Keta, Otilija D.; Vidosavljević, Marija Z.; Incerti, Sebastien; Ristić Fira, Aleksandra M.; Petrović, Ivan M.
Abstract: Purpose: Investigation of effects on DNA of γ-irradiated human cancer cells pretreated with free radical scavengers is aimed to create reference data which would enable assessment of the relative efficiency of high linear energy transfer (LET) radiations used in hadron therapy, i.e. protons and carbon ions. Materials and methods: MCF-7 breast and HTB177 lung cancer cells are irradiated with γ-rays. To minimize indirect effects of irradiation, dimethyl sulfoxide (DMSO) or glycerol are applied as free radical scavengers. Biological response to irradiation is evaluated through clonogenic cell survival, immunocytochemical and cell cycle analysis, as well as expression of proteins involved in DNA damage response. Results: Examined cell lines reveal similar level of radioresistance. Application of scavengers leads to the rise of cell survival and decreases the number of DNA double strand breaks in irradiated cells. Differences in cell cycle and protein expression between the two cell lines are probably caused by different DNA damage repair mechanisms that are activated. Conclusion: The obtained results show that DMSO and glycerol have good scavenging capacity, and may be used to minimize DNA damage induced by free radicals. Therefore, they will be used as the reference for comparison with high LET irradiations, as well as good experimental data suitable for validation of numerical simulations.